Effect of cyclic fastening–unfastening and interruption of current flowing through a snap fastener electrical connector on its resistance - Leśnikowski Jacek; Szewczyk Monika (AUTEX Research Journal, 2025)
Integrating electronic components into smart textiles revolutionised the field, with snap fasteners often serving as electrical connectors. This study investigated the electrical and mechanical durability of sewn-on snap fasteners under cyclic fastening–unfastening and interruption of direct current (DC) flowing through them. The available literature indicates that snap fasteners can endure repeated mechanical stresses; however, there is a lack of data regarding their behaviour during the cyclic interruption of DC flow. This research fills this gap by analysing changes in electrical resistance and unfastening forces over 10,000 cycles of current interruption. Results indicate that larger snap fasteners offer greater mechanical resistance, although size does not significantly impact electrical durability. For example, the average force needed to release the snap fasteners after 10,000 cycles is reduced to 5 N for large snap fasteners and 2 N for the small ones. This article also discusses how the substrate fabric and the type of thread used to attach the snap fastener affect the electrical strength of the tested connector. The findings presented offer valuable insights for designing and selecting materials in future smart textile applications, thereby enhancing the robustness and functionality of wearable electronics.